2022
DOI: 10.3389/fbioe.2022.862495
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond as a Cytokine Sponge in Infectious Diseases

Abstract: Cytokine release syndrome (CRS) is a systemic inflammatory response resulting in overexpression of cytokines in serum and tissues, which leads to multiple-organ failure. Due to rapid aggravation of symptoms, timely intervention is paramount; however, current therapies are limited in their capacity to address CRS. Here, we find that the intravenous injection of highly purified detonation-synthesized nanodiamonds (DND) can act as a therapeutic agent for treating CRS by adsorbing inflammatory cytokines. Highly pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Specifically designed nanocarriers can neutralize pro-inflammatory cytokines by selectively delivering agents that temper specific inflammatory pathways, thereby curtailing the hallmark cytokine storm of sepsis. One such innovation is Seokho Kim’s diamond nanodiamond (DND) structure, a potent pan-cytokine adsorbent, which effectively clears pivotal cytokines including IL-1β, IL-6, IL-8, and TNF-α . Breaking from tradition, Luo’s group pioneered a wireless, battery-free vagus nerve stimulator, underpinned by an implantable high-performance hydrogel nanogenerator (HENG) (Figure A).…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
“…Specifically designed nanocarriers can neutralize pro-inflammatory cytokines by selectively delivering agents that temper specific inflammatory pathways, thereby curtailing the hallmark cytokine storm of sepsis. One such innovation is Seokho Kim’s diamond nanodiamond (DND) structure, a potent pan-cytokine adsorbent, which effectively clears pivotal cytokines including IL-1β, IL-6, IL-8, and TNF-α . Breaking from tradition, Luo’s group pioneered a wireless, battery-free vagus nerve stimulator, underpinned by an implantable high-performance hydrogel nanogenerator (HENG) (Figure A).…”
Section: Research Hotspots Of Nanotechnology In Sepsismentioning
confidence: 99%
“…Intravenous injection of pure detonation-synthesized nanodiamond has been promoted as a cytokine absorber in the treatment of cytokine release syndrome (CRS) in the treatment COVID-19 [ 219 ]. This system has been tested on mice and exhibit low toxicity, fast-acting cytokine-absorption, and good mice survival rates.…”
Section: Drug Delivery Applicationmentioning
confidence: 99%
“…This section discusses some applications of the bare ND for the study and treatment of blood and blood components. Thus, the use of ND for controlled modification of the inflammatory and immune response is discussed [88][89][90]. It has been observed that detonation ND modifies the activity of neutrophils from the site of acute inflammation.…”
Section: In Vitro Studies Of the Interaction Of Nd With Blood Cells A...mentioning
confidence: 99%
“…The possibility of using this effect to develop an effective nanovaccine against the H7N9 Influenza virus is discussed [89]. On the other hand, uncoated highly purified detonation ND was applied as a cytokine "sponge" in infectious diseases [90]: intravenously administered ND has been proposed a therapeutic agent for treatment of cytokine release syndrome (CRSa systemic inflammatory response resulting in overexpression of cytokines, which leads to poliorganic failure) by adsorbing inflammatory cytokines. Successful ND inactivation of key cytokines in the blood plasma of CRS patients with COVID-19, pneumonia and septic shock has been demonstrated [90].…”
Section: In Vitro Studies Of the Interaction Of Nd With Blood Cells A...mentioning
confidence: 99%
See 1 more Smart Citation